Kinetic of Methane Hydrate Formation in Micro- and Nanodroplets - Manteghian, Mehrdad; Dorosti, Reza; Mohammadi, Abolfazl (Asian Journal of Chemistry, 2012)
In this research, the kinetic of hydrate formation from a microdroplet or nanodroplet is investigated. The shrinking core model is used for predicting of hydrate growth on a droplet. In this model, it assumed that the nucleation was started on the outer surface of water droplet and the direction of hydrate growth is into the center of the droplet. Diffusion of the gas molecules through the gas film surrounding the droplet, diffusion through the hydrate layer and reaction with the outer surface of unreacted water is the steps of hydrate formation in shrinking core model. The reaction rate constant of methane molecules with water droplet (k) is extracted from literature. Using shrinking core model showed that, in nanodroplets and droplets smaller than 1 μm, reaction of gas molecules with water droplet is the main resistance in the hydrate formation. By increasing the size of water droplets, the resistance of diffusion through the hydrate film was increased and in droplet larger than 100 μm, the main resistance of hydrate formation was diffusion of gas molecules. By increasing the temperature, the effect of chemical reaction in hydrate formation resistances was increased.